NEUROSIENCE DAN PENGALAMAN KEAGAMAAN ( SPRITUAL) KASUS KORUPSI - Hammi Latifah (Hikmah, 2017)
Day by day people are always faced with deviant behavioral symptoms. Lying is no longer in a personal capacity even though it includes self-denial, but is done through its power, the power of the public. A power which, according to a healthy soul and a clear mind, is to carry out the mandate of the people. What is the relitasnya? That is a lie to lie covering these (political) power processes is a "structural lie".A power structure controlled by "liars". As the one held in anti-corruption institutions, along with 720 personal staff in the corruption eradication commission (KPK), is always faced with an increasingly creative mode of corruption as a product of mental lying.Day after day corruption experienced the dynamics of its mode, run systematically, synergistically, calmly and "solemnly". The age around forty years down marks some young, wealthy people, with a pragmatic lifestyle and hedonist. They are the middle class with the predicate scholarship a number of public and private universities. As explained in neurosciences that the soul as well as spirituality is the product of the human brain although the mechanisms for bringing the two are different.It is interesting to understand the necessity of recruiting candidates for the professional leaders of this state organization by finding out what is the relationship between a healthy brain, a close connection to the meaning of life and spirituality. The theory of neurosciences is highly recommended, at least learn from interpreting the perpetrators of corruption including the class of learned, a method of recruitment of public leaders capable of producing human elected. And neuroscience can be a government policy to involve a spiritual neuroscience approach in doing the fit and proper test of a country's stakeholder candidate. So that eventually hopefully through neuroscience and ISHA can contribute to the form of recruitment methods that can capture healthy and sane leaders of the brain, the fruit of the presence of God in the human brain. Keywords: neuroscience, spritual, corruption, ISHA.